PERANAN KOMPOSIT UNTUK PESAWAT TERBANG - SUZANNA H (JURNAL MITRA MANAJEMEN, 2013)
ABSTRACTTechnological progress can not be separated from the advancement of research inmaterials innovation and management capabilities (manufacturing method), to be used as auseful product.Recent decades the development of some of the material found so by nature(characteristics) are different, but can produce new materials with new force that is anamalgamation of the properties of each material is better known as a composite material.One of the material / materials, which are now considered to be highly superior to theworld's aircraft or Aeronautical ie between fiber composite materials (fiber) and metalsAluminum (Al) as a matrix material and produce a strong, lightweight and rigid, as the basicmaterial properties of the alloys.Keywords: Aircraft Material, Structure and Properties of Composite for Aircraft